Clinical manual for the oncology advanced practice nurse - Camp-Sorrell, Dawn; Cope, Diane G.; Hawkins, Rebecca A. (Rebecca Ann) 1957- (Oncology Nursing Society, 2022)
"Patients with cancer can experience an array of complex medical issues during and following treatment, whether from the cancer itself, cancer therapy, or existing comorbidities. Advanced practice nurses providing care to this population need to be able to assess and treat acute and chronic conditions to promote favorable outcomes in symptom management and quality of life. This fourth edition builds upon the prior editions to address the nuances associated with assessing and intervening on symptoms to provide informed patient care. It has undergone extensive revision and incorporates new chapters to reflect current practice. Written by experts in oncology nursing and pharmacology, this comprehensive text serves as a quick reference guide for the diagnosis and treatment of emergent and ongoing problems occurring in patients with cancer. Symptoms are grouped by body system, and content is extensively cross-referenced to allow easy identification of symptoms to determine a medical diagnosis. This manual provides a detailed yet resource to guide busy practitioners within their practice"--